MENTAL ACCOUNTING DAN VARIABEL DEMOGRAFI : SEBUAH FENOMENA PADA PENGGUNAAN KARTU KREDIT - Mahastanti, Linda Ariany (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2012)
The aim of this research is to analysis relationships of demographic factor towards mental accounting inusing credit card. Demographic factors which use in this research is sex, age, and income. Researcher takesthe sample from the employees of Bumi Arta bank, Tbk. Surakarta which have and use credit card. To analysisthe primary data, the writer use chi-square test as a tool. The result of this research shows that sex and incomehave relationships on mental accounting in using credit card.Keywords : Demographic factors, mental accounting, credit